The challenges faced by the parents in self-reflection among Chinese Muslim Yunnan, China - Dan, Ma Dan; Yasin, Maizura; Saharuddin, Norzihani (Human Resource Management Academic Research Society, 2024)
Educational “involution” and educational anxiety in China is an obvious social phenomenon, which has been concerned by many researchers. Parents' self-reflection also faces challenges in raising their children. This study uses in-depth interviews and literature analysis to collect data, aiming to explore the challenges Muslim parents face in self-reflection and their understanding and coping with these challenges, and to gain a deeper understanding of the narrative details of parents' reflection in specific contexts, so as to more systematically understand the struggles and coping of Hui Muslim parents in reality. This study finds that parents' self-reflection is influenced by the internal and external environment of the family, and parents also face challenges in their choice and judgment of educational value in the process of raising children. Parents' self-reflection based on different family realities also shows adaptability and flexibility in facing challenges. This study can provide reference and support for the follow-up research on family counseling strategies and parent training programs.